PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Zulkifli Zulkifli; Latifah Latifah (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
This research is aimed to analyze the influence of Corporate Governance, Firm Size, and Profitability, dan Firm Growth to Dividend Policy in the manufacture Corporations which are registered in Indonesian Stock Exchange in period of 2017 – 2019, both in partially or simultaneously. The variables which will be studied: corporate governance that is proxied with the number of board commissioners and institutional ownership, firm size, profitability and firm growth. The Populations in this research are the manufacture corporations which are registered in BEI in period of 2017-2019. The samplings in the research are 20 manufacture corporations that are achieved by the technique of purposive sampling. Analysis of research data used multiple linier regression method that was assisted by SPSS 23.0 software. This study used multiple linier regression method showed that partially profitability variable and the firm growth were influencing significantly to the dividend policy, meanwhile the number of board commissioners, institutional ownership, and firm size were not influencing to the dividend policy. The result of this research simultaneously showed that the number of board commissioners, institutional ownership, firm size, profitability, and firm growth were influencing positively and significantly to the dividend policy.